Teaching strategies to develop communication in an EFL class for primary school - Bermejo Bravo, Andrea Gabriela; Criollo Columba, Mayra Alejandra
The topic of this research is ?Teaching Strategies to Develop Communication in an EFL class for Primary School?. This work has been developed taking into consideration that the speaking skill is often considered the most difficult skill to develop in EFL learning because getting students respond in a foreign language class is a problem that most language teachers face. This research describes the necessity of students? interaction and students? oral participation in class. This work is focused on finding some criteria and insights about how to find the specific strategies which can help teachers keep their students participating interactively. To clarify doubts about what strategies can be applied in EFL classes, it was necessary to obtain information through a survey applied to fifteen elementary school children from nine to ten years old, and other one applied to four primary school English teachers who contributed to our research due to their experiences as teachers. Consequently, the bibliographic as well as the qualitative methods were used to enrich this research and obtain scientific knowledge in order to determine the strategies that can be useful to reinforce the speaking skill in an EFL classroom.